2019
DOI: 10.3390/antiox8110509
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Magnesium in the Secondary Phase After Traumatic Spinal Cord Injury. A Prospective Clinical Observer Study

Abstract: In the secondary injury phase after traumatic spinal cord injury (TSCI), oxidative stress and neuroinflammatory responses at the site of injury constitute crucial factors controlling damage extent and may serve as potential therapeutic targets. We determined Magnesium (Mg) serum concentration dynamics in context with the potential of neurological remission in patients with TSCI as Mg is suspected to limit the production of reactive oxygen species and reduce lipid peroxidation. A total of 29 patients with acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Previous studies indicated that peripheral trace element dynamics and concentration changes in the trace element biomarkers are associated with the clinical outcome after TSCI ( Heller et al, 2019 , 2020 ; Sperl et al, 2019 ; Seelig et al, 2020 ). It was thus hypothesized that there might be a close correlation between serum Se, SELENOP and SELENBP1 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that peripheral trace element dynamics and concentration changes in the trace element biomarkers are associated with the clinical outcome after TSCI ( Heller et al, 2019 , 2020 ; Sperl et al, 2019 ; Seelig et al, 2020 ). It was thus hypothesized that there might be a close correlation between serum Se, SELENOP and SELENBP1 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…They can trigger different regulatory functions through specific ion channels and enzymes. Recent studies have revealed that membrane significant fluxes of Mg 2+ can affect the cell’s metabolic cycles and function [ 83 ]. In the central nervous system, Mg 2+ is known to maintain calcium homeostasis.…”
Section: Magnesium and Cellular Biology Of Scimentioning
confidence: 99%
“…level to 40-60% with a 10-15% decrease in total Mg 2? level; which may affect the entry of glutamate and calcium into the presynaptic neuron (Sperl et al 2019;Cook et al 2011). This results in neurodegeneration and cell death as secondary to brain injury (Institute of Medicine (US) Committee on Nutrition 2011).…”
Section: Magnesium and Neurological Diseasesmentioning
confidence: 99%